2022
DOI: 10.1002/jcla.24409
|View full text |Cite
|
Sign up to set email alerts
|

Novel immune‐related signature based on immune cells for predicting prognosis and immunotherapy response in clear cell renal cell carcinoma

Abstract: Background Clear cell renal cell carcinoma (ccRCC) is the most common malignant tumor of the kidney and is characterized by poor prognosis. We sought to build an immune‐related prognostic signature and investigate its relationship with immunotherapy response in ccRCC. Methods Immune‐related genes were identified by ssGSEA and WGCNA. The prognostic signature was conducted via univariate, least absolute shrinkage and selection operator, and multivariable Cox regression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Previous reports have shown that TIMP3 is associated with the development of a variety of tumors [27,28]. In previous reports, we observed that TIMP3 showed high expression in pancreatic cancer tissues [29], and TIMP3 was upregulated in cervical cancer cell lines and cervical squamous cell carcinoma tissues. Shaker et al created a model in which they noted that the expression level of TIMP3 was increased in normal cervical cells during carcinogenesis as compared to parental HCK cells [30].…”
Section: Discussionmentioning
confidence: 57%
“…Previous reports have shown that TIMP3 is associated with the development of a variety of tumors [27,28]. In previous reports, we observed that TIMP3 showed high expression in pancreatic cancer tissues [29], and TIMP3 was upregulated in cervical cancer cell lines and cervical squamous cell carcinoma tissues. Shaker et al created a model in which they noted that the expression level of TIMP3 was increased in normal cervical cells during carcinogenesis as compared to parental HCK cells [30].…”
Section: Discussionmentioning
confidence: 57%